PENGARUH DAYA TARIK WISATA TERHADAP LOYALITAS DESTINASI MELALUI KETERIKATAN EMOSIONAL STUDI PADA MUSEUM KERATON SUMENEP - Diva Fanesintya; Nurita Andriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The Sumenep Palace Museum faces a decline in visitors from 43,302 (2022) to 25,850 (2023). This can occur due to decreasing tourist interest in visiting, ineffective promotions, lack of updates to tourist attractions, and increasingly strong competition from other destinations that are more modern and in demand by visitors. This study examines how tourist attractions affect visitor loyalty through their emotional ties to the Sumenep Palace Museum. Using quantitative methods, the sampling technique used is non-probability sampling through accidental sampling or purposive sampling. Researchers collected data from 100 visitors (minimum age 17 years, visited at least 2 times) through questionnaires and analyzed them using the PLS-SEM technique. Three main variables were studied: destination attractiveness, emotional attachment, and visitor loyalty. The results of the study indicate that tourist attractions have a positive and significant influence on destination loyalty. In addition, emotional attachment acts as a mediating variable in the relationship between tourist attractions and destination loyalty.